Adolescencia y embarazo en el hospital base de Chepen Enero – Diciembre de 1991 - Inga Reátegui, Eliana (1992)
In our time the study of pregnancy and its outcome in teenagers is of great interest because of the risks it brings, I actually listed as high risk obstetrics pregnancy. From January 19 to December 31, 1991 1593 births attended in gynecology and obstetrics Hospital Chepén service, giving birth during this period 103 adolescents; the study was compared with other similar series, conducted at national and international level The 103 cases accounted for 6.47% of all births, demographics were single and living together, coming mostly from urban areas - marginal and urban, with primary-school education, economically dependent on their parents and home ele from the point of Work view, which are factors that contribute to risk obstetrics. Most of our pregnant adolescents had their menarche most often between 12 and 14; worth mentioning that a high percentage of abortions background, 20% reported having had an abortion and 15% on two occasions, the vast majority of spontaneous type (70%). Given these results are proposed as alternative mass media programs in coordination with higher education institutions, students and teachers being responsible for programming. 62% of the cases had pre-natal control at different institutions; most of them came to term (93%), being most of them served by internal Obstetrics. The casuistry studied reveals a greater number of complications during the first trimester of pregnancy which decrease as gestational age advances, a fact that can be influenced by the pre-natal (62%) control. Most teens had an onset of spontaneous labor, with a duration of normal labor (53%); striking in our series the number of normal deliveries (84%) with a significant percentage of prolonged labor (17%), which can be explained by inadequate handling of labor due to lack of supervision Internal by professional specialty. Most newborns (64%) were born with low Apgar score, evaluated in the first minute of life; obtaining five minutes vigorous children (85%) weighing considered within normal limits at 89.3% of cases; only el4.85% were premature. Most teenagers started their sex at a very early stage (between 11-16 years) in a 7.7% ignoring aspects related to sexuality. Some information about it was received mostly by teachers and friends. These results suggest the need for counseling and training for parents. On the other hand, the contraceptive method used was the pace, followed by condom usage time was less than one year and, being 95% of them wish to use some method later. Finally, 63% expressed the desire of pregnancy, while more than a third of what they saw as an unwanted pregnancy. 21% want to have 3 or more children so this group should emphasize knowledge about sexuality, family planning and responsible parenthood. Importantly, 44% do not define their birth interval, a variable that should be included as a risk factor.